Perkembangan Karir Di Dunia Kerja - Mirna Ari Mulyani (Wardah, 2015)
A person who intends to enter the world of work, preferably from beginning to prepare   variety of requirements that are needed in the conditions and make a decision to enter the workplace. Understanding of career guidance services in counseling services, has been mentioned at the beginning of the employment information. Position information that has been entered, although they have been getting training. New information are still useful for adjusting employment options and also the choices of educational programs and training that is relevant to the world of work in the future